2012
DOI: 10.1556/ceugeol.55.2012.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and tectonic evolution of the Kiskunhalas-NE fractured hydrocarbon reservoir, South Hungary

Abstract: The Kiskunhalas-NE (KIHA-NE) fractured hydrocarbon reservoir is part of the structurally rather complex crystalline basement of the Great Hungarian Plain. In the course of petrologic and thermometric examinations various rock types of the investigated area have been classified and characterized. There are four basic lithological units in the area. In the lowest structural position orthogneiss is common, which according to its petrographic features is assumed to be identical to the orthogneiss body of the adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…This means a 5-10 km difference in formation depth depending on the one-time geothermal gradient. This result, together with presence of the extensional mylonites, implies that the study area evolved in an extensional stress regime following the thermal peak; blocks of different metamorphic conditions became juxtaposed along a shear zone at a depth corresponding to ~455 °C (Nagy and M. Tóth, 2012). The entire rock column behaved uniformly during the following tectonic development; at shallower positions it deformed in a brittle way.…”
Section: Geological Backgroundmentioning
confidence: 74%
See 2 more Smart Citations
“…This means a 5-10 km difference in formation depth depending on the one-time geothermal gradient. This result, together with presence of the extensional mylonites, implies that the study area evolved in an extensional stress regime following the thermal peak; blocks of different metamorphic conditions became juxtaposed along a shear zone at a depth corresponding to ~455 °C (Nagy and M. Tóth, 2012). The entire rock column behaved uniformly during the following tectonic development; at shallower positions it deformed in a brittle way.…”
Section: Geological Backgroundmentioning
confidence: 74%
“…Geochemical data infer weathering of the phyllite body under surface conditions. The latest examinations (Nagy and M. Tóth, 2012) based on the macroscopic, microscopic and thermometric studies of borecore samples identified four main rock types. The ideal rock column was defined using all available borecore specimens.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Molnár et al (2014a) extended this detachment horizon using well-log data of numerous neighbouring wells, suggesting the presence of a low-angle fault zone. Based on the investigations of Nagy and M Tóth (2012), there are four basic lithologies in the Kiskunhalas-NE basement area. In the lithological column between the uppermost graphitic carbonate phyllite and the lowermost orthogneiss formations, there is *200°C of peak metamorphic temperature deviation.…”
Section: Possible Geodynamical Interpretationsmentioning
confidence: 99%
“…Összefoglalóan, a János hal ma-dóm egy egységes or togneisz blokk, amelynek e gyik fő jellemzője a külön bö ző kőzet típusú és meta morf fejlődéstörténetű, meta bá zi kus kemiz musú xeno litok és xe no kristályok jelen léte (3. áb ra). TÓTH 2012;FISER-NAGY et al 2013, 2014FISER-NAGY 2013) négy fő kőzettípust kü lö nítettünk el, melyek a ku tak ban tapasztalt szomszéd sá gi és mélységviszonyok a lap ján az ideális kőzetoszlop ban alulról felfelé a követke zők: ortogneisz, ortogneisz mi lonit, grafitos gneisz milo nit és grafitos karbonátfillit. A legalsó ismert szerkezeti hely zet ben lévő ortogneisztest minden szöveti tulajdon sá gában meg egyezik a János halma területen részletezettel (4. ábra, a).…”
Section: Táblázat a Használt áSványrövidítések Whitney And Evans (2010) Alapján Table I Mineral Abbreviations After Whitney éS Evans (201unclassified